2017
DOI: 10.1007/s10493-017-0155-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of pathogens in ticks infesting cattle in Nampula province, Mozambique

Abstract: Ticks are ectoparasites that can act as vectors of a large number of pathogens in wild and domestic animals, pets, and occasionally humans. The global threat of emerging or re-emerging tick-borne diseases supports the need for research focused in the zoonotic transmission, especially in countries like Mozambique where rural populations are in close contact with domestic animals. The present study aims to: (1) identify tick species infesting cattle from Monapo and Nacala Porto, districts of Nampula province, Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 62 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…Our findings add to available data on the prevalence of rickettsial pathogens in ticks within the southern African region. Other countries in the region which have reports of tick surveys for Rickettsia infection include Zimbabwe ( 49 ), Botswana ( 52 ), Mozambique ( 53 ), and South Africa ( 54 58 ) with prevalence ranging from as low as 3% to as high as 77%. This study also adds to the growing data on tick-borne ( 41 , 42 , 59 61 ) and tick-associated ( 62 , 63 ) zoonotic pathogens within Zambia.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings add to available data on the prevalence of rickettsial pathogens in ticks within the southern African region. Other countries in the region which have reports of tick surveys for Rickettsia infection include Zimbabwe ( 49 ), Botswana ( 52 ), Mozambique ( 53 ), and South Africa ( 54 58 ) with prevalence ranging from as low as 3% to as high as 77%. This study also adds to the growing data on tick-borne ( 41 , 42 , 59 61 ) and tick-associated ( 62 , 63 ) zoonotic pathogens within Zambia.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Copodella have been identified from blood, ticks and soil samples (Han et al, 2018;Jiang et al, 2018;Matsimbe et al, 2017;Olmo et al, 2011;Yuan et al, 2012) but as per our best knowledge, this is the first study in which Colpodella have been identified from the fecal samples of zoo felines of Northeast China. Researchers have realized the pathogenic importance of Colpodella after two case reports from China (Jiang et al, 2018;Yuan et al, 2012) where Colpodella has been found to associate with neurological symptoms and Babesia sp.…”
Section: Discussionmentioning
confidence: 81%
“…The unusual presence of R. africae in R. microplus ticks may have been due to the co-occurrence of the two tick species, R. microplus and A. variegatum, on cattle. As the ticks here were collected partially engorged, the presence of R. africae in R. microplus may have been due to bacteria circulating in cattle blood picked up by engorging ticks, or to cross-contamination with R. microplus ticks co-feeding next to infected A. variegatum [33,34].…”
Section: Discussionmentioning
confidence: 99%